Density, Social Networks and Job Search Methods: Theory and Application to Egypt - Jackline Wahba; Yves Zenou (The Research Institute of Industrial Economics (IUI), 2004)
The aim of this paper is to study the impact of the size and the quality of social networks on the probability to find a job. We first develop a theoretical model in which individuals are embedded within a network of social relationships. Workers can obtain information about jobs via employed friends belonging to his/her social network. Workers can be either uneducated or educated. We show that, conditional on being employed, the probability to find a job through social networks, relative to other search methods, increases and is concave with the size of the network. The effects are stronger for the uneducated. There is however a critical size of the network above which this probability decreases. We also show that the probability to find a job through friends and relatives decreases with the local unemployment rate. We test empirically these theoretical findings for Egypt using the 1998 Labor Market Survey. The empirical evidence supports the predictions of our theoretical model.
Keywords: J23; O12; 330; Education; Social Networks; Search Methods; Arbeitsuche; Schätzung; Ägypten; Soziales Netzwerk